Strengthening Posyandu Through Kader Entrepreneurs in North Sumatera - Gunawan, Roni; Sutandra, Lagut (Jurnal Riset Hesti Medan, 2020)
Posyandu cadres are an important part of the program journey in Indonesia which has long been integrated into various programs. Including in the health program, cadres are the spearhead of community health activities based on community empowerment through Integrated Service Posts (Posyandu). The problem of Posyandu operational costs and economic cadres often become obstacles for developing Posyandu, so that the Posyandu productivity decreases. Therefore, it is necessary to strengthen entrepreneurship for Posyandu cadres to increase Posyandu funding while increasing the family economy. This study uses a qualitative approach to portray efforts to strengthen Posyandu through entrepreneurship in Posyandu cadres. Posyandu cadres are the main informants whose information is obtained through in-depth interviews, after which in-depth interviews with stakeholders will be conducted. The results showed that Posyandu cadres who have entrepreneurship are still active in running Posyandu and have good performance, and are classified as active cadres. Entrepreneurs that are being carried out by cadres are still individual and do not affect their performance as cadres, in fact entrepreneurs who are run a lot help posyandu activities, cadres can help household financing while helping Posyandu operations. Cadre business is going well because the government is strengthening cadres in training to improve the quality of entrepreneurship, then supported by licenses issued by the district. Business incubation also impacts cadre business.